Conflict Elements in Nenek Novel by Razali Endun - Md Zain, Rosnani; Nik Muhamad Affendi, Nik Rafidah (Malay Literature, 2018)
This article discusses the conflict found in the novel Nenek . Nenek won the prestigious Hadiah Sastera Perdana literary prize in 2014. The novel sparked controversy when it was declared the winner. Critics felt that Nenek did not meet the criteria and was awarded the prize due to political interference. The objective of this study is to classify and analyse elements of conflict in Nenek . This study will look at conflicts in the novel from the perspective of the humanistic psychologist Abraham Maslow. Humans are never free of problems. These problems and conflicts cause people to struggle, and they are in a constant state of dilemma where they are unable to make the right decisions and solve problems. Human beings are forced to deal with conflicts to disperse the problems that upset their lives instead of avoiding them. In the end, conflicts involving the characters are handled wisely. The study finds that Nenek touches on several types of conflict, such as political conflicts, economic conflicts and family conflicts. The study shows that Razali Endun is able to depict contemporary society by depicting such conflicts in his novels. Keywords: Nenek , Hadiah Sastera Perdana 2014, conflict, Maslow Humanistic